1986
DOI: 10.1021/jm00157a005
|View full text |Cite
|
Sign up to set email alerts
|

New antiarrhythmic agents. 2,2,5,5-Tetramethyl-3-pyrroline-3-carboxamides and 2,2,5,5-tetramethylpyrrolidine-3-carboxamides.

Abstract: N-(omega-Aminoalkyl)-2,2,5,5-tetramethyl-3-pyrroline- or -pyrrolidine-3-carboxamides were acylated on the primary amino group of the side chain by means of reactive acid derivatives (acid chlorides, activated esters, phthalic anhydrides, phthalimide, 2-alkyl-4H-3,1-benzoxazin-4-ones) or they were alkylated by forming the Schiff bases and subsequent sodium borohydride reduction. Other tetramethyl-3-pyrrolinecarboxamide compounds were synthesized by acylating the aminoalkyl compounds with 2,2,6,6-tetramethyl-3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 1 publication
1
25
1
Order By: Relevance
“…Regarding the structure-activity relationship (SAR), the principal ring compound protecting activity greatly varied depending on the substituent. Compounds 1, 2 exhibited good activity, compound 3 exhibited limited activity, 4, 5 and H-2641 with cardioprotective activity 8 were inactive in PARP inhibitory assay. The ω-amino S-alkylated compounds 15a-d exhibited better protection activity than the S-ethyl one (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the structure-activity relationship (SAR), the principal ring compound protecting activity greatly varied depending on the substituent. Compounds 1, 2 exhibited good activity, compound 3 exhibited limited activity, 4, 5 and H-2641 with cardioprotective activity 8 were inactive in PARP inhibitory assay. The ω-amino S-alkylated compounds 15a-d exhibited better protection activity than the S-ethyl one (4).…”
Section: Resultsmentioning
confidence: 99%
“…6,7 In our laboratory we have synthesized 4-quinazolinone derivative, H-2641 as an antiarrhythmic drug candidate. 8 It was a real challenge to test and compare this compound with basic quinazolines 1-3 ( Figure 1) on PARP inhibitory activity assay as well as synthesizing new quinazolinone derivatives attached to 1-oxyl-2,2,5,5-tetramethyl-2,5-dihydro-1H-pyrrole or 1-oxyl-2,2,6,6-tetramethyl-1,2,3,6-tetrahydropyridine and their amine precursors, because these rings exhibited radical scavenging activity and protected against oxidative stress. This fact can be a significant contribution in designing new PARP inhibitors against cell damage induced by antiviral 11 and anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the N-oxides and N-hydroxyl amines of both series of compounds were shown to have no antiarrhythmic effect but to be less toxic than the active amines. Similarly, Hankovszky et al 4 showed that the nitroxides and hydroxylamines prepared from different compounds chemically close to Class I antiarrhythmic agents, showed no or decreased antiarrhythmic effects relative to the amino compounds.…”
Section: Introductionmentioning
confidence: 95%
“…observations prompted us to test our experimental drug H-2545 and its metabolite H-2954 (Scheme 2: compounds 3 and 4) in order to determine whether they can prevent the acute deterioration of cardiac function following DOX administration [10]. It was reported that compound 3 ( Fig.…”
Section: Introductionmentioning
confidence: 99%